Model Mitigasi Risiko Likuiditas pada Fintech Syariah P2P Lending : Liquidity Risk Mitigation Model in Fintech Sharia P2P Lending - Ardiansyah, Jefri; Muhammad Yazid (Litera Academica Publishing, 2025)
The rapid growth of Sharia-based peer-to-peer (P2P) lending fintech in Indonesia is accompanied by major challenges, particularly liquidity risk that may disrupt platform stability. This study aims to identify the sources of liquidity risk in Islamic fintech and formulate a mitigation model aligned with Sharia principles. A qualitative approach with descriptive-analytical and case study methods was employed. Data were collected from literature review, official reports by the Financial Services Authority (OJK), and observation of practices in selected Islamic P2P platforms. The findings indicate that liquidity risks are primarily caused by borrower payment delays, maturity mismatch, panic withdrawals by lenders, and the limited availability of Sharia-compliant liquidity instruments. The proposed mitigation model includes the use of Sharia reserve funds based on tabarru’, automated payments via blockchain-based smart contracts, funding diversification through fintech sukuk, and early warning systems powered by AI. This study recommends that regulators issue specific guidelines on liquidity risk management in Islamic fintech and promote inter-institutional collaboration to ensure a resilient and sustainable Islamic financial ecosystem.